Anesthetic management of patients undergoing cardiac myxoma resection: a single-center retrospective analysis - Qi, Wei; Yu, Xiao-lu; Yang, Da-xuan; Hu, Xu-kai; Chen, Jun-ping; Yao, Yun-tai; , the Evidence in Cardiovascular Anesthesia (EICA) Group (Frontiers in Cardiovascular Medicine, 2023)
Background: Myxomas are the most common primary cardiac tumors. Intracardiac myxomas, although benign, could cause serious consequences such as tricuspid or mitral valve obstruction, hemodynamic collapse, and acute heart failure, which pose challenges during anesthetic management. The current study was designed to summarize the anesthetic management of patients undergoing cardiac myxoma resection. Methods: This study was performed retrospectively from the perioperative period of patients who underwent myxoma resection. Patients were divided into two groups according to whether the myxoma prolapsed into the ventricle (group O) or not (group N) to evaluate the impact of tricuspid or mitral valve with obstruction. Results: 110 patients, aged 17–78 years, undergoing cardiac myxoma resection between January 2019 and December 2021 were collected, and their perioperative characteristics were recorded. In the preoperative evaluation, common clinical symptoms included dyspnea and palpitation, whereas embolic events occurred in 8 patients, including 5 (4.5%) cerebral thromboembolic events, 2 (1.8%) femoral artery, and 1 (0.9%) obstructive coronary artery. According to the echocardiography, left atrial myxoma was detected in 104 (94.5%) patients, the average dimension of myxoma was 4.03±1.52cm in the largest diameter, and 48 patients were divided into group O. During intraoperative anesthetic management, hemodynamic instability occurred in 38 (34.5%) patients after anesthesia induction. More patients in group O had hemodynamic instability (47.9% vs. 24.2%, p = 0.009) than in group N. The mean postoperative length of stay in the hospital was 10.64±3.01 days, and most of the patients made an uneventful postoperative recovery. Conclusions: Anesthetic management for myxoma resection can be composed by assessing the myxoma, particularly the echocardiography evaluation and preventing cardiovascular instability. Typically, tricuspid or mitral valve with obstruction is a premier ingredient in anesthetic management.